Various Cognitive Linguistic Abilities - : Concepts, Structures and their Activation - Omer Mahmood Karim; Bnar Abduljabbar Jamil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This research, entitled (Various Cognitive Linguistic Abilities - Concepts, Structures and their Activation), consists of an introduction and two sections, in the theoretical section, a set of concepts and topics were clarified, such as: the concept of competence and cognitive linguistic abilities, and this has been divided into two branches: 1- Basic abilities, which include both cognitive abilities and pragmatic abilities.2- Communication abilities. In the second section we have two subsections, one is practical in which, it was mentioned how to participate and interact between competence and cognitive abilities. Many examples are provided and at the end of the research the results and the list of references are presented.